Settingbezogene Gesundheitsförderung und Prävention in der digitalen Transformation Transdisziplinäre Perspektiven - Dockweiler, Christoph; Stark, Anna Lea; Albrecht, Joanna (Gesundheitsforschung. Interdisziplinäre Perspektiven, 2023)
Our everyday lives, which are largely shaped in particular settings, are being increasingly affected by technological innovations. For example, work processes and organisational structures are becoming increasingly digital, which creates new health opportunities but also poses risks. From the perspective of science, practice and politics, this book reflects on and discusses what the digital transformation of settings as well as the availability of new digital tools mean for setting-related health promotion and prevention. Against this background, a new conceptual understanding of digital settings is presented in the context of the setting approach. This book presents the latest research findings, practice-based projects and current professional experiences. With contributions by Joanna Albrecht | Jennifer Apolinário-Hagen | Anja Bestmann | Berit Brandes | Dirk Bruland | Heide Busse | Julia Anna Deipenbrock | Christoph Dockweiler | Gudrun Faller | Susanne Giel | Ludwig Grillich | Beate Grossmann | Rahim Hajji | Stephanie M. Helmer | Laura Herrera Bayo | Friederike Keipke | Jessica Kemper | Marion Kiem | Lena Köhler | Kilian Krämer | Simon Lang | Änne-Dörte Latteck | Matthias Meyer | Kristin Mielke | Markus Möckel | Saskia Muellmann | Eva Obernauer | Nadine Pieck | Uwe Prümel-Philippsen | Inke Ruhe | Christel Salewski| Philip Santangelo | Ulrike Scorna | Mariella Seel | Jelena Sörensen | Anna Lea Stark | Elitsa Uzunova | Gunnar Voß | Stefan Winter